Determination of intrarenal resistance index (RI) in patients with multiple myeloma - Schiemann, U (BioMed Central, 2010)
BACKGROUND: Renal impairment is a common complication of multiple myeloma occuring in up to 50% of patients at some stage in their disease. Due to occurrence of cast nephropathies we hypothesized circulatory dysregulation (vasoconstriction) in the kidneys with measurable elevation of the resistance index among these patients which would have a diagnostic impact. SUBJECTS AND METHODS: 36 patients with treated multiple myeloma (21 females, 15 males, mean age 61.6 ± 8.5 years) were prospectively examined by conventional abdominal ultrasound with focussed investigation of the kidneys. First, length of the organs, parenchymal width and characterization of parenchymal echogenicity were determined. Then, intrarenal RI values were measured in segmental and arcuate arteries, respectively, in both kidneys. Additionally, serum creatinine, BUN and GFR of each patient were evaluated. RI values were compared to values of 78 healthy control subjects. RESULTS: Mean renal RI was 0.68 ± 0.07 which was slightly higher than in controls with 0.62 ± 0.05, but without statistical significance. Due to the laboratory analyses patients were subdivided in those with normal (group 1, n = 21) and those with impaired (group 2, n = 15) renal function. In both groups kidney size and parenchymal width were normal. Significant more group 2 patients (60%) revealed hyperechogenic par enchyma than group 1 patients (24%) (p < 0.01). Mean renal RI indices were 0.67 ± 0.06 (right) and 0.69 ± 0.06 (left) in group 1 patients and 0.71 ± 0.08 (right) and 0.71 ± 0.07 (left) in group 2 patients and showed no significant difference (p = 0.06 and 0.15). CONCLUSION: Renal RI values are not significantly elevated in patients with multiple myeloma even in those with renal impairment so that no hints to a relevant vasoconstriction could be evaluated. RI seems not to be a relevant parameter for the diagnosis of cast nephro pathy of multiple myeloma patients. Routinely performed ultrasound examination should be more focussed on the qualification of parenchymal echogenicity.